2003
DOI: 10.1159/000072489
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Hormonal Treatment and Radiotherapy for Prostate Cancer

Abstract: Adjuvant hormone treatment with radiotherapy has been demonstrated in two studies (Bolla and RTOG 8531) to be beneficial in patients with locally advanced prostate cancer. However, the vast majority of patients with early prostate cancer can be cured with radiotherapy alone. Subset analysis combining RTOG 8610 and RTOG 8531 has demonstrated a survival benefit only for patients with a biopsy Gleason score ≤6 after short-term neoadjuvant hormonal therapy. The results of ongoing research will further clarify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Understanding flexibility and constraints in the expression and evolution of aging requires a careful analysis of key aging metrics (1, 18, 19). We used a maximum-likelihood framework for estimating two metrics that, together, describe the pattern of senescence for a population: the initial adult mortality rate ( IMR , the risk of death at onset of adulthood) and the rate of aging ( RoA , the rate of increase in the age-specific mortalities with advancing adult age).…”
mentioning
confidence: 99%
“…Understanding flexibility and constraints in the expression and evolution of aging requires a careful analysis of key aging metrics (1, 18, 19). We used a maximum-likelihood framework for estimating two metrics that, together, describe the pattern of senescence for a population: the initial adult mortality rate ( IMR , the risk of death at onset of adulthood) and the rate of aging ( RoA , the rate of increase in the age-specific mortalities with advancing adult age).…”
mentioning
confidence: 99%
“…It was reported that adjuvant therapy with the LHRH analogue goserelin, started at the beginning of external irradiation treatment and continuing for 3 years, improved the 5‐year overall survival of patients with locally advanced prostate cancer. It is, therefore, clear that uncertainties exist regarding factors such as optimal timing, sequencing and type of HT (Wachter et al , 2003).…”
Section: Critical Discussion Of Treatment Rationalementioning
confidence: 99%
“…Here we respond to the challenge of Wachter (11), who noted that the evolutionary theories of aging generally fail to be able to predict the characteristics of mortality trajectories. To do this, we apply a recent development in state-dependent life history theory (12) that accounts for activity, the generation of cellular damage through metabolism and reinforcement of damage, repair of damage, and the mortality consequences of damage.…”
mentioning
confidence: 96%